Health promotion of hospital workers throug workplace gymnastics based on the pilates method - Araujo, Aureni Cicera de; Monte, Lindinalva Brasil (Seven Editora, 2024)
The growth of work-related illnesses has aroused the interest of researchers in quality of life at work, with a strong relationship between worker - work environment and work - illness. In this context, Occupational Gymnastics (OGS) has been an alternative in reducing and/or preventing illness and the Pilates method has emerged as an effective tool with possibilities for practicing exercises with an approach and appreciation of the integration of mind and body, improving well-being and quality of life. Considering the study carried out with members of the multi-professional teams at a public teaching hospital in the state of Pará, with favorable results, the construction of a program of care for the civil servant with physical activities related to guided practices, subsidized the elaboration of an educational tool through a guide to workplace gymnastics with guided exercises based on the pilates method, aiming to reduce daily stress, sedentary lifestyle and improve the general functionality and integration of the work team. DOI:https://doi.org/10.56238/sevened2024.001-017